Searching for New Z-DNA/Z-RNA Binding Proteins Based on Structural Similarity to Experimentally Validated Zα Domain - Bartas, Martin; Slychko, Kristyna; Brázda, Václav; Červeň, Jiří; Beaudoin, Christopher A; Blundell, Tom L; Pečinka, Petr (International journal of molecular sciences, 2022)
Z-DNA and Z-RNA are functionally important left-handed structures of nucleic acids, which play a significant role in several molecular and biological processes including DNA replication, gene expression regulation and viral nucleic acid sensing. Most proteins that have been proven to interact with Z-DNA/Z-RNA contain the so-called Zα domain, which is structurally well conserved. To date, only eight proteins with Zα domain have been described within a few organisms (including human, mouse, Danio rerio, Trypanosoma brucei and some viruses). Therefore, this paper aimed to search for new Z-DNA/Z-RNA binding proteins in the complete PDB structures database and from the AlphaFold2 protein models. A structure-based similarity search found 14 proteins with highly similar Zα domain structure in experimentally-defined proteins and 185 proteins with a putative Zα domain using the AlphaFold2 models. Structure-based alignment and molecular docking confirmed high functional conservation of amino acids involved in Z-DNA/Z-RNA, suggesting that Z-DNA/Z-RNA recognition may play an important role in a variety of cellular processes.
Keywords: Z-RNA; konformace proteinů; Structure-Activity Relationship; RNA; simulace molekulární dynamiky; vztahy mezi strukturou a aktivitou; DNA vazebné proteiny; Protein Binding; Models, Molecular; Molecular Dynamics Simulation; konformace nukleové kyseliny; vazba proteinů; Amino Acid Sequence; molekulární modely; interakční proteinové domény a motivy; Zα domain; Protein Interaction Domains and Motifs; protein binding; vazebná místa; simulace molekulového dockingu; DNA, Z-Form; proteiny vázající RNA; bioinformatics; Binding Sites; sekvence aminokyselin; DNA-Binding Proteins; Nucleic Acid Conformation; Z-DNA; Protein Conformation; RNA-Binding Proteins; Molecular Docking Simulation